Optimum relative concentrations of nitrogen, phosphorus and sulfur in coffee fertilization in a Dark-Red Latosol, at Machado, MG, Brazil - Venegas, Victor Hugo Alvarez; Freire, Francisco M.; Guimarães, Paulo Tácito G. (Pesquisa Agropecuaria Brasileira, 2014)
The N-P-S equilibria in coffee (Coffea arabica L.) fertilization (Catuaí cultivar) in a Dar-Red Latosol, "cerrado" phase, at Machado, MG, were studied under greenhouse conditions. The equilibria were tested in the N-P, P-S and S-N relations and the treatments were chosen according to Richard's Cut Method. The three cut values were defined, for N and P, as a function of the phosphate maximum adsorption, and for S, as a function of the sulfate maximum adsorption. In each nutrient binary relation and each cut, four equilibria were studied. The treatment effects were evaluated 20 months after planting by measuring total dry weight. The leaf N, P and S concentrations were also determined. For each nutrient relation, the lack of the third anion limited the plant growth, mainly for N in the cuts of the P-S relation. For the vegetative growth, the cut 0.4 was more effective than the cut 0.2 and equivalent or more effective than the cut 0.8. ln the N-P relation, when more N was added, the P requirement became higher. In the P-S relation, the optimum relative concentrations indicated that the demand of S increased with the addition of P. In the same way, in the S-N relation, for higher levels of N, more S was required. In general, for the best cut (0.4), the best equilibrium of the three nutrients was obtained with the application of 165 ppm of N, 80 ppm of P and 44 ppm of S. Some informations about the leaf N, P and S concentrations are presented.